2014
DOI: 10.1155/2014/753953
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular Conduction Delay in the Second Trimester Measured by Fetal Magnetocardiography

Abstract: Introduction. Fetal AV block in SSA/Ro pregnancies is generally not seen before 18-week gestation and onset is rare after 28-week gestation. If complete AV block appears, it is believed to be irreversible. The purpose of the study was to evaluate precise electrophysiological AV conduction from 18-week gestation onwards. Patients and Methods. 21 fetuses of pregnant women with collagen vascular diseases were included in the study group and 59 healthy fetuses served as controls. In addition to fetal echocardiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…It is urgently necessary to define the susceptible populations, from both maternal and fetal aspects. [ 2 15 26 27 28 29 30 31 32 33 34 35 36 37 ] The efficacy of current approaches for preventing the CHB progression in affected fetus and recurrence in subsequent pregnancy as well as other autoimmune-mediated damages is still controversial. The parameters to weigh out the risk and benefit remain to be determined.…”
Section: Urrent D Ilemma In Cmentioning
confidence: 99%
See 1 more Smart Citation
“…It is urgently necessary to define the susceptible populations, from both maternal and fetal aspects. [ 2 15 26 27 28 29 30 31 32 33 34 35 36 37 ] The efficacy of current approaches for preventing the CHB progression in affected fetus and recurrence in subsequent pregnancy as well as other autoimmune-mediated damages is still controversial. The parameters to weigh out the risk and benefit remain to be determined.…”
Section: Urrent D Ilemma In Cmentioning
confidence: 99%
“…Furthermore, recent studies showed that fMCG can be effectively used in the prenatal diagnosis of atrial bigeminy (conducted and blocked), 2:1 AVB, CAVB, delayed AV conduction, PQ segment prolongation, and different types of long QT syndrome. [ 32 33 34 35 ]…”
Section: Iagnosis and H Eart mentioning
confidence: 99%
“…В настоящее время магнитокардиографы используются для изучения нормальной работы сердца [4] и диагностики его различных заболеваний [5][6][7][8][9][10][11][12][13][14]. При этом, как правило, МКГ-обследования проводят в магнитно-экранированном помещении, ослабляющем внешние электромагнитные помехи от двух до пяти порядков [15,16].…”
Section: Introductionunclassified